Literarna dejavnost slovenskih društev v drugih delih nekdanje Jugoslavije - Žitnik Serafin, Janja (Jezik in slovstvo, 2014)
By way of introduction, the article thematises the role of literature in safeguarding the original national and cultural identity of a migrant/minority community and the problem of the discrimination of language varieties of Slovenian used in internal communication by members of Slovenian minority groups in Croatia, Serbia, Bosnia and Herzegovina, Macedonia and Montenegro, where Slovenes and their descendents have established numerous cultural societies. In the continuation, the article focuses on the activities of these societies related to literature. The most common such activities are presentations of Slovenian literature in society bulletins, book presentations by visiting Slovenian authors from Slovenia and neighbouring countries, and recitals of Slovenian poetry at society celebrations in honour of Slovenian national festivals. Some societies also encourage translation activities, but they are less active regarding original literary attempts by their members. The author of the present paper attributes this to their lack of knowledge of standard or "literary" Slovenian, and to a certain self-restraint in using their language variety for literary purposes.
Keywords: slovenski izseljenci; nekdanje jugoslovanske republike; slovenska društva; književnost; literature